Анализ проблем информационной безопасности в компьютерных сетях - Гавриленко, А.; Караваев, В. (ХНУРЕ, 2019)
This article is devoted to information security in computer networks. The article discusses the security problems of computer networks and describes the recommendations for fixing vulnerabilities
Keywords: кибербезопасность; политики безопасности; MikroTik; Ubiquiti; шифрование; VPN; IDS; Firewall